Assessment of phototherapy-induced hypocalcemia and its correlation with urinary calcium excretion in term and preterm newborns with neonatal hyperbilirubinemia: A cross-sectional study with controls - Gupta, Raksha; Singh, Davinder; Yadav, Meetu; Panda, Prateek Kumar; Nagaraj, Niranjan; Bana, Sailen Kumar (Indian Journal of Child Health, 2018)
Introduction: Although hypocalcemia is often proposed to be associated with phototherapy in both term and preterm newborns, its exact incidence, clinical significance, and underlying mechanism still remain to be elucidated. Objective: The objective of this study was to determine the prevalence of hypocalcemia and its etiopathogenesis in terms of urinary calcium excretion. Methods: This study was carried out in a tertiary care center in North India with 50 neonates (29 term and 21 preterm) in the test group receiving single surface phototherapy. The other 50 age, sex, and gestational age-matched neonates were taken as controls who did not receive phototherapy. Serum calcium levels at 0 and 48 h and urinary calcium/creatinine ratio (mg/mg) at0 and 24 h of starting phototherapy were determined in both the groups and compared. Results: Total 12 preterm (57.1%) and 9 term newborns (31%) developed hypocalcemia after 48 h of phototherapy. The mean difference of serum ionized calcium between two groups was statistically significant at 48 h (4.58 mg/dl in the test group vs. 4.94 mg/dl in the control group, p